Programa Mais Médicos and its repercussion in the media: what should be informed and for whom? - Mateus Aparecido de Faria; Cristianne Maria Famer Rocha; Liara Saldanha Brites; Angela Maria Grando Machado; Claiton Agnaldo Ribeiro Santos; Neuza de Freitas Raupp Cechinel; Rossana dos Santos Rocha Mativi (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2018)
The PMM - Programa Mais Médicos [More Doctors Program] was established in Brazil in 2013. Since it was announced, the question of its viability, results and continuity has been debated by the Brazilian society. The aim of this article is to identify and analyze the media discursive productivity in the first year (May 2013 to July 2014) of the PMM. An exploratory and documentary study of articles published in a weekly magazine of great circulation in Brazil (IstoÉ) was developed by means of a search for reports on its virtual site with descriptors related to the Program and 34 articles were selected in 31 editions from one month before the setting up of PMM by "medida provisória". The magazine noticed the arrival of foreign professionals, the xenophobic acts committed by Brazilian medical associations, and the category's corporative protection. The PMM contributes greatly to improve the health of the population and to satisfy its needs, but it reproduces the medical centrality, disregarding that the work of other health professionals have also been complicated in areas neglected by the State.